Development and evaluation of miniature electrodes for electrochemical measurements in a CO2 top of line corrosion environment. (3rd October 2019) - de Carvalho, S.S.; Hua, Y.; Barker, R.; Huggan, Michael; Gomes, J. A. C. P.; Neville, A.
ABSTRACT: Top of line corrosion (TLC) is a degradation mechanism which establishes itself in 'wet gas' pipelines under significant temperature difference between the internal fluid and the outer pipe wall. Laboratory evaluation of TLC is based predominantly on the mass loss method which is an averaging approach. Hence, a real-time and spatially resolved corrosion response would add an extra dimension in terms of corrosion measurement. This work presents a new apparatus to explore the ability of a miniature three-electrode cell to provide instantaneous corrosion measurements in a TLC scenario. The electrochemical system is integrated into a buoyancy-driven flow TLC setup and is used to monitor instantaneous corrosion rates for X65 carbon steel over 20h through a combination of linear polarisation resistance, electrochemical impedance spectroscopy and Tafel measurements. The electrochemical responses are compared with gravimetric results under identical conditions and generating repeatable, accurate and instantaneous data to provide more insight into TLC mechanism.